In-depth characterization of as-deposited and annealed Fe-W coatings electrodeposited from glycolate-citrate plating bath. (20th January 2018) - Mulone, A.; Nicolenco, A.; Hoffmann, V.; Klement, U.; Tsyntsaru, N.; Cesiulis, H.
Abstract: Fe-W coatings with 4, 16 and 24 at.% of W were electrodeposited under galvanostatic conditions from a new environmental friendly Fe(III)-based glycolate-citrate bath. This work aims to find correlations between composition including the light elements, internal structure of the electrodeposited Fe-W alloys and functional properties of material. The obtained alloys were characterized by Glow Discharge Optical Emission Spectrometry (GD-OES), Scanning Electron Microscopy (SEM) with Energy Dispersive X-ray Spectroscopy (EDS), Transmission Electron Microscopy (TEM), and X-ray Diffraction (XRD). Compositional depth profiles of 10 μm thick coatings obtained by GD-OES show that the distribution of metals is uniform along the entire film thickness, while SEM imaging depicted the presence of cracks and O- and W-rich areas inside the Fe-W coating with 4 at.% W. In the samples with 16 and 24 at.% of W, oxygen and hydrogen are present mostly at the surface about 1 μm from the top while traces of carbon are distributed within the entire coatings. With increasing W content, the structure of the coatings changes from nanocrystalline to amorphous which was shown by XRD and TEM analysis. Also, the surface of coatings becomes smoother and brighter, that was explained based on the local adsorption of intermediates containing iron and tungsten species. Annealing experiments coupled with XRD analysis show that the thermal stability of Fe-W alloys increases when the W content increases, i.e. the coating with 24 at.% W retains the amorphous structure up to 600 °C, where a partially recrystallized structure was observed. Upon recrystallization of the amorphous samples the following crystalline phases are formed: α-Fe, Fe2 W, Fe3 W3 C, Fe6 W6 C, and FeWO4 . Hence, the Fe-W coatings with higher W content (>25 at.%) can be considered as suitable material for high temperature applications. Highlights: In-depth structural analysis of as-deposited and annealed Fe-W alloys was carried out. Internal cracks with O-rich areas were found for low-W content alloy. Compositional depth profiles were obtained for Fe, W, C, H and O by GD-OES. Mixed nanocrystalline-amorphous phase was found for Fe-16W and truly amorphous phase for Fe-24W alloy. Fe-W-C phases were formed after annealing of Fe-W alloys having ≥16 at.% of W.